ICU data management - A permissioned blockchain approach - Guimarães, Tiago André Saraiva (2020)
Since its origin in finance, blockchain have been revolutionizing data storage and sharing in many other sensitive areas. Being the focus of Permissioned Blockchains around privacy, confidentiality, immutability, interoperability and reliability, it fits perfectly within the data requisites of healthcare. Even more, with the surge of new iterations of more recent implementations based on smart-contracts/chaincode that has its focus on increasing efficiency and usability and ease of implementation. Intensive Medicine an area with such high data complexity and throughput, and high incidence of medical error and patient injury. As such, it's imperative the continuous research and implementation of new technologies that can make pertinent knowledge available through reliable and accurate data, thus providing appropriate problem-solving skills to physicians. This paper presents a solution, as part of the Intelligence Decision Support Systems for Intensive Medicine (ICDS4IM) project, which objective is to increase accuracy, confidentiality and value to data from vital sensors and monitors by assuring its immutability and controlled oversee.